EVALUATION OF LIPID PROFILE AND LIVER FUNCTION PARAMETERS IN OBESE AND NON-OBESE HYPERTENSIVE INDIVIDUALS ATTENDED TERTIARY CARE TEACHING HOSPITAL - M., PRASAD RAO; JALEM, SPURGEON RAJ; KUMAR, BARLA BSV SATYA; SANGAM, SMRUTI (International Journal of Current Pharmaceutical Research, 2023)
Objective: In this study, lipid profile parameters and liver function parameters were measured and correlated in hypertensive obese and non-obese patients who were attended a tertiary care teaching hospital. Methods: This study is a retrospective observational, cross-sectional study over the course of a year in a tertiary care hospital. All adult patients with hypertension, both obese and non-obese, are included in the study population. The study involved 150 participants in total, including obese and non-obese people (71 men and 79 women). Standard techniques were used to assess the serum levels of TG, TC, LDL, HDL, and liver enzymes such SGOT, SGPT, bilirubin, and ALP. Moreover, BMI was calculated for both study groups. The association between elevated lipid profile markers and liver enzyme abnormalities was assessed by correlation analysis. Results: Out of 150 samples size comprises 75 obese and 75 non-obese individuals, 71 males and 79 females were reported in the current study. Our study gives very good association between lipid profiles to almost all LFT and the highest is shown between HDL, LDL and VLDL to all LFT. There was a high significant difference was noticed between the obese and non-obese individuals in relation to bilirubin (D) concentration, SGOT and SGPT between the two groups P<0.0001. The levels of albumin were lowered and the significant variations were noticed between the two groups. The mean values of cholesterol, LDL and triglycerides were very high in obese individuals than non-obese individuals and the HDL was lower in obese individuals. Conclusion: The study found that liver function variables and abnormal lipid profiles were highly prevalent in obese hypertension patients. In participants with dyslipidemia, increased liver enzymes were seen more frequently.